Website Creation as Means of Digitizing MSME Products for School Uniforms at Agung's Collection - Eko Wahyudi; Anggraini Puspita Sari; Firza Prima Aditiawan (Future Science, 2022)
The development of digital technology provides opportunities for micro, small, and medium enterprises (MSMEs) to utilize online media in marketing strategies that were initially only conventional in the hope of increasing the income of MSME actors. Agung's Collection is an MSME actor who was selected as a partner for community service activities financed by the East Java